(untitled) (INNOVATIVE ECONOMY, 2021)
Kovshova I.O., Babych Yu.V. STRATEGIC DIRECTIONS OF DEVELOPMENT OF INNOVATIVE MARKETING IN THE MARKET OF HIGH TECHNOLOGIES Purpose. The aim of the article is defining strategic directions for the development of innovative marketing in the high-tech market in order to increase sales of goods or services, increase the efficiency of enterprises and analyse potential markets. Methodology of research. The following methods were used in the research process: abstract and logical - to formulate the concepts of innovative marketing, high technologies and strategies of innovative marketing; analysis and synthesis - to identify certain parts of the innovative marketing strategy and their proper application in the high technology market; economic and statistical - to study the strategic directions of innovative marketing and to establish a quantitative impact on the high technology market; comparative - to compare the development trends of strategic areas of innovative marketing in 2016 and 2020. Findings. The essence of the characteristics of innovative marketing in the high-tech market is deepened and the most effective strategic directions of innovative marketing development of today are identified: software promotion, artificial intelligence, video marketing, personalization and conversational marketing. It is substantiated that to ensure innovative marketing activities, it is important for the company to constantly monitor the market and new tools that will bring goods or services to a new level. It is established that the five areas of innovative marketing have been identified as significantly influencing the marketing tools of high-tech enterprises, artificial intelligence programs are included in all areas of the marketing industry and are actively used by marketers to process, recognize and analyse voice, text, images and decision making. Options for the use of artificial intelligence in the marketing activities of enterprises are substantiated and the main trends of further development are formed. Originality. It is substantiated that these strategic directions of development of innovative marketing today (software promotion, artificial intelligence, video marketing, personalization and conversational marketing), in contrast to existing strategic directions of development, increase sales of goods and services, increase brand awareness, build trust and improve communication with potential and real customers. Practical value. The results of the conducted study can be used by high-tech companies in Ukraine and around the world to increase market competitiveness and bring the product or service to a new level. It will also increase sales of goods or services and increase the efficiency of enterprises. Key words: innovative marketing, enterprise, directions of development, technology market, video marketing, artificial intelligence, marketing.